Theologies of the Land and State of Israel: The Role of the Secular in Jewish and Christian Understandings - Langer, Ruth (Studies in Christian-Jewish Relations, 2011)
Christians and Jews have tended to approach theological understandings of Israel through different categorizations of what constitutes appropriate topics for theology. Separation of religious and political realities has been an aspect of Christian culture since the fourth century, but it was never a native separation for Judaism. Thus, contemporary Christian theologians have attempted to develop understandings of Jewish relationship to the land that excludes its political aspects. From a Jewish perspective, this amounts to a recasting of Judaism according to a foreign set of values, one that devalues the potential (if not yet actualized) theological meanings inherent in contemporary Jewish sovereignty over its historical homeland. Progress in dialogue about Israel requires confronting this difference directly.